Multi-ethnic citizens in a multi-ethnic state: Constructing state–citizen relations through ‘difference’ in the Adivasi Janajati scholarship programmes in Nepal - Pradhan, U (Taylor and Francis, 2019)
In 1990, the Constitution of Nepal declared Nepal a multi-ethnic (bahujatiya) country. This newly transformed state promised better inclusion of marginalised groups through special provisions. How has this been operationalised, and what does this mean in practice for the members of the groups concerned? Drawing on fieldwork in the Nepal Foundation for Development of Indigenous Nationalities (NFDIN), this paper argues that the Nepali state’s moral and political obligation to address long-standing concerns about group-based inequalities has opened up intriguing new spaces to perform and redefine state–society relations. Within these new spaces, categories of difference are constantly invoked and experienced, where both the state and citizens come to co-constitute each other in a variety of new ways.